Differentiation of benign and malignant breast lesions using shear wave elastography; estimation of the most accurate parameters - Godlewska, Antonina; Andryszak, Natalia; Pasiuk-Czepczyńska, Anna; Godlewski, Dariusz; Ruchała, Marek; Czepczyński, Rafał (Journal of Medical Science, 2025)
Aim. Breast elastography is a sonographic imaging technique, used additionally in diagnosis of breast lesions. The place of shear-wave elastography (SWE) in breast imaging is still unclear, the literature is limited and the interpretation of SWE results is undefined. The aim of our study was to evaluate the diagnostic accuracy of SWE in relation to histopathology and to estimate the probable cut-off value of SWE parameters, which would indicate malignancy.Material and methods. The study included 53 consecutive patients with suspicious breast lesions. Each patient underwent the SWE of the breasts, and every visualized lesion was biopsied.Results. 56 lesions were found; 24 of them were classified as malignant and then confirmed as cancer. Malignant tumours presented with significantly higher SWE parameters, except elasticity value of fat tissue surrounding the lesion (Efat), as compared to benign lesions. The optimal cut-off point was determined using the Youden Index. The receiver-operating characteristic curve (ROC) curve analysis established cut-off values of: Emax 63.4 kPa (p < 0,000001, AUC 0.94), Emean of 40.8 kPa (p = 0.000003, AUC 0.87), Emax/Efat ratio of 5.64 kPa (p < 0.000001, AUC 0.92) and Emean/Efat ratio of 4.31 kPa, (p = 0.000006, AUC 0.86), which indicate malignancy. The sensitivity and specificity were 100% and 87.5% respectively for Emax and 100% and 75% for Emean. There were no differences in SWE parameters between cancer subtypes.Conclusions. In our study SWE indicated correctly all malignant lesions. Moreover, we established cut-off values of SWE parameters that may be useful in differentiating malignant and benign breast lesions.